Bioethicist upheld Hippocratic oath - Woo, Elaine (The Gazette (Montreal), 2008)
"This was his most significant work. ... It has been very influential in shaping the thinking of bioethicists on the doctrine of informed consent," said Alexander Capron, a University of Southern California professor of law and medicine who was a co-author of books with [Jay Katz]. Katz said the Tuskegee subjects had been "exploited, manipulated and deceived. They were treated not as human subjects but as objects of research." "There is persistent confusion between research and (clinical) practice and the obfuscation of the two," Katz told the Los Angeles Times in 1994. "You cannot use people - or you should not use people - as means for others' ends and for ends that might ultimately even be good."